The complete sequence of dystrophin predicts a rod-shaped cytoskeletal protein. - Koenig, M; Monaco, A; Kunkel, L (1988)
The complete sequence of the human Duchenne muscular dystrophy (DMD) cDNA has been determined. The 3685 encoded amino acids of the protein product, dystrophin, can be separated into four domains. The 240 amino acid N-terminal domain has been shown to be conserved with the actin-binding domain of alpha-actinin. A large second domain is predicted to be rod-shaped and formed by the succession of 25 triple-helical segments similar to the repeat domains of spectrin. The repeat segment is followed by a cysteine-rich segment that is similar in part to the entire COOH domain of the Dictyostelium alpha-actinin, while the 420 amino acid C-terminal domain of dystrophin does not show any similarity to previously reported proteins. The functional significance of some of the domains is addressed relative to the phenotypic characteristics of some Becker muscular dystrophy patients. Dystrophin shares many features with the cytoskeletal protein spectrin and alpha-actinin and is a large structural protein that is likely to adopt a rod shape about 150 nm in length.